EVALUATING COMBINING ABILITY AND HETEROSIS EFFECTS ON YIELD, ASSOCIATED TRAITS, AND YELLOW RUST RESISTANCE IN WHEAT (TRITICUM AESTIVUM L.) - YASEEN, R; MAHMOOD, T; BHATTI, WA; BHATTI, JA; AKHTAR, N; RAZA, N; BIBI, T (Biological and Clinical Sciences Research Journal, 2024)
Wheat is a considerable energy source for the people of Pakistan and many other countries. Yellow rust is the most unpropitious biotic stress for wheat yield. The research was conducted to study the combining ability, heterosis and response of genotypes for yellow rust resistance. For this impetus, eight wheat genotypes, namely (five genotypes viz; Dharabi-11, Hp-1, Ehsan-16, Pak-13 and Morocco) were kept as lines and three genotypes viz; Markaz-19, Borlauge-16 and Fakhar-e-Bhakar used as testers. Lines X Testers matting design developed fifteen F1 hybrids sown in proper symmetry for crossing during rabi season 2020-21 at the university research farm, PMAS-Arid Agriculture University Rawalpindi, during 2020-21. During Rabi 2021-22, developed hybrids along with the eight parents in a randomized complete block design (RCBD) using three replications with plant-to-plant and row-to-row distances of 15cm and 25cm, respectively. Morocco was used as a spreader and sown after every five rows; two rows are the border of each replication. Data was recorded for the traits viz. flag leaf area, canopy temperature, chlorophyll content, days to maturity, 1000 grain weight, seed yield per plant and disease score. Mean value showed a maximum in Markaz-19 for flag leaf area, Pakistan-13 for chlorophyll content among parents. HP-1 x Markaz-19 showed maximum seed yield per plant (29.27 g). Minimum disease score was observed in Borlague-16.